Supplementary Material for: Evaluation of Disease Burden in Parkinson's Disease for Individuals Aged 60 and Older - figshare admin karger (2628495) (2025)
OBJECTIVE: To evaluate global trends in Parkinson's disease (PD) burden (measured by disability-adjusted life years, DALYs) among individuals aged ≥60 years from 1990 to 2021, and project future trends to 2046. METHODS: Using Global Burden of Disease (GBD) 2021 data, we analyzed age-standardized DALY rates (ASDR) via Joinpoint regression. Age-Period-Cohort (APC) modeling disentangled age, period, and birth cohort effects. Decomposition analysis quantified contributions of population growth, aging, and epidemiological changes. Bayesian APC (BAPC) projected DALYs to 2046. RESULTS: Global PD DALYs increased from 2.55 million (95% UI: 2.33–2.79) in 1990 to 6.80 million (6.04–7.49) in 2021. ASDR rose annually by 0.31% (AAPC=0.31%, 95% CI: 0.29–0.33), with pronounced male predominance (male ASDR 2021: 861.9 vs female: 498.9; male-to-female ratio: 1.73). Highest ASDR occurred in High-middle SDI regions (683.7), lowest in Low SDI (612.9). APC analysis revealed disease risk peaked at ages 85–94 and increased with successive birth cohorts. Decomposition identified population growth as the primary driver of DALY increases (81.55% globally), exceeding contributions from aging (8.74%) and epidemiological shifts (9.71%). BAPC projections indicated rising absolute DALYs (+104% by 2046) but declining ASDR (607.3 by 2046), with widening gender disparities. CONCLUSION: PD burden escalates globally due to demographic aging and population growth. Urgent international collaboration is needed for targeted interventions, particularly in high-burden regions and for older males.